CSR terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Fanesa Rena Revaliana; Gideon Setyo Budiwitjaksono (Journal of Management and Bussines (JOMB), 2022)
This research aims to examine the the effect of Corporate Social Responsibility on Firm Value with financial performance as an intervening variabel in food and beverage sub sector manufacturing listed on Indonesia Stock Exchange for the 2018-2020 period. The research method used PLS (Partial Least Square). The technique used to determine the sample in this research is purposive sampling and obtained 48 samples for 3 years research. The result showed, CSR and financial performance variables had an effect on firm value with p values of 0.007 < 0,05 and 0.000 < 0.05. Financial performance as a mediating variable also has an influence in mediating CSR and firm value with p values of 0.021 < 0.05. However, the result shown by p values of 0.707 > 0.05 showed that CSR has no effect on financial performance. Conslusion, Keywords: CSR, Food and Beverage, Firm Value, Financial Performance